2003
DOI: 10.1063/1.1542923
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-terminated defects in ion-implanted silicon probed by monoenergetic positron beams

Abstract: Hydrogen-terminated vacancies in Siϩ -implanted Si were studied by means of positron annihilation. After the Si ϩ -ion implantation, hydrogen atoms were introduced into the damaged region using a hydrogen plasma ͓hydrogen-atom treatment ͑HAT͔͒. Monoenergetic positron beams were used to measure Doppler broadening spectra of the annihilation radiation and the lifetime spectra of positrons. It was found that the line shape parameter, S, corresponding to the annihilation of positrons trapped by vacancy-type defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…This S parameter is an index of the number and size of vacancy-type defects [7]. The details of the PAS measurement system are described elsewhere [10], [11]. Effective minority carrier lifetime was measured using a 9.35-GHz microwave transmittance measurement system and analyzed on the basis of carrier diffusion and annihilation theory [12], [13].…”
Section: Methodsmentioning
confidence: 99%
“…This S parameter is an index of the number and size of vacancy-type defects [7]. The details of the PAS measurement system are described elsewhere [10], [11]. Effective minority carrier lifetime was measured using a 9.35-GHz microwave transmittance measurement system and analyzed on the basis of carrier diffusion and annihilation theory [12], [13].…”
Section: Methodsmentioning
confidence: 99%
“…Almost all the positrons annihilate from the trapped state by V 2 in the Si-implanted Si. 23 For the as-received sample, although the lifetime of positrons in the strained-Si layer was close to that of positrons trapped by V 2 , the value of (S,W) was different from the characteristic value of (S,W) for V 2 . For annealing below 950°C, the (S,W) value seemed to move toward the value for defect-free Si with increasing temperature, but for annealing above 1000°C, it started to approach the (S,W) value for defect-free Ge.…”
Section: Resultsmentioning
confidence: 88%
“…For the as-implanted sampIe, for example, four blocks were used, where the first to third blocks corresponded to the damaged regions, and the fourth block corresponded to the defect-free region. For ion-implanted Si or damaged Si, it is often observed that the damaged region shifts toward the surface with increasing annealing temperature [15]. However, as shown in Fig.…”
Section: Resultsmentioning
confidence: 96%